Testing the core-competency model of multi-product exporters - Eckel, C; Iacovone, L; Javorcik, B; Neary, J (John Wiley and Sons Ltd, 2016)
We review the implications of the “core-competence” model of multi-product firms, including the “market-size puzzle”: for most countries, the world market is much larger than the home market, while the costs of accessing foreign markets are relatively low; hence the model predicts that most domestic firms should export more of their core products than they sell domestically; yet, in practice, we do not observe this. Extending the model to allow for investment in export market penetration resolves the puzzle, and Mexican data confirm its predictions: in particular, only the largest firms exhibit the dominance of exports over home sales.